Senjata Energi Terarah: Tinjauan Aksiologis: Directed Energy Weapons: An Axiological Review - Sujani, Nano; Yogaswara, Y.H. (Undiksha, 2024)
This research discusses the development of Directed Energy Weapons (DEW) in the context of the philosophy of defense science, with a focus on axiological aspects. The background of the study highlights social and ethical changes resulting from the advancement of science, while the lack of script understanding also affects the meaning that can be achieved through language. Philosophy, as an initiator of critical thinking, plays a crucial role in liberating humans from the limitations of knowledge.The research uses a qualitative descriptive approach with the researcher as the main instrument. The focus is on DEW, a weapon that uses concentrated electromagnetic energy, creating debates on ethics and law. The laws of war and international agreements are considered incapable of accommodating the technological advancements of DEW, raising concerns about violations of legal agreements and international humanitarian law. The research results indicate that the axiological perspective in the philosophy of defense science is needed to guide the development of DEW technology. Evaluation is done through teleological and deontological approaches, emphasizing moral goals and obligations. The ethical and moral implications of DEW development are examined by considering their impact on humanity, human rights, and environmental sustainability. This approach reinforces the urgency of forming an Ethical Code for the development and use of DEW, emphasizing clear definitions, involvement of independent experts, restrictions on sales and technology transfer, and military ethics training. Additionally, the research suggests international dialogue to build consensus and address common issues related to the development of this technology. By integrating axiological aspects of the philosophy of defense science, this research provides a holistic view of DEW development, considering moral and ethical values as guidelines in its utilization.